What influences Latino grocery shopping behavior? Perspectives on the small food store environment from managers and employees in San Diego, California. Issue 2 (3rd March 2016) - Sanchez-Flack, Jennifer C.; Baquero, Barbara; Linnan, Laura A.; Gittelsohn, Joel; Pickrel, Julie L.; Ayala, Guadalupe X.
ABSTRACT: To inform the design of a multilevel in-store intervention, this qualitative study utilized in-depth semistructured interviews with 28 managers and 10 employees of small-to-medium-sized Latino food stores ( tiendas ) in San Diego, California, to identify factors within the tienda that may influence Latino customers' grocery-shopping experiences and behaviors. Qualitative data analysis, guided by grounded theory, was performed using open coding. Results suggest that future interventions should focus on the physical (i.e., built structures) and social (i.e., economic and sociocultural) dimensions of store environments, including areas where the two dimensions interact, to promote the purchase of healthy food among customers.